Ossiculoplasty for Malleus Bar with Incudostapedial Disconnection and Fused Incudomalleolar Joint - Kanazawa, Yuji; Matsuura, Hitomi; Aiso, Natsumi; Nakai, Masako (Case Reports in Otolaryngology, 2020)
Malleus bar is an abnormal bony connection between the malleus handle and the posterior wall of the tympanic cavity. We report a patient with a malleus bar and another malformation of the ossicles. An 11-year-old boy presented with hearing impairment since early childhood. Computed tomography (CT) revealed a malleus bar with an incudostapedial disconnection in the right ear. At tympanoplasty, the malleus bar was first identified and removed. A fused malleus-incus, not visible on the preoperative CT, was found intraoperatively. Therefore, the fused malleus-incus was removed; then, the ossicular chain was reconstructed, resulting in an improved postoperative hearing level. On preoperative CT, the disconnected incudostapedial joint had been identified, whereas the fused malleus-incus had not. Given the variations in the malleus bar anomaly of the middle ear, the surgical procedure for ossiculoplasty should be adapted intraoperatively based on any findings not visible on the preoperative CT.